Pregnancy outcomes and factors affecting the clinical effects of cervical cerclage when used for different indications: A retrospective study of 326 cases - Ruizhe Chen; Xiaoxiu Huang; Baohua Li (Elsevier, 2020)
Objective: To compare pregnancy outcomes resulting from the use of cervical cerclage for different indications and investigate factors that might influence the clinical effects of cervical cerclage. Materials and methods: This was a retrospective study of pregnant women who received cervical cerclage in The Women's Hospital, Zhejiang University School of Medicine, China. Patients were divided into three groups: a history-indicated group; an ultrasound-indicated group and a physical examination-indicated group. The pregnancy outcomes of the three groups were then compared. Univariate and multivariate logistic regression analysis were performed to assess the independent risk factors. Results: Statistical differences were evident when the history-indicated group and the ultrasound-indicated group were compared with the physical examination-indicated group for gestational age at delivery [37.3(33.3-38.9), 35.4(28.9-38.4) vs. 26.1 (24.3-28.4) weeks, respectively, P < 0.05], percentage of cases delivered at < 28 weeks of gestation (13.4%, 20.3% vs. 74.3%, respectively, P < 0.05), percentage of cases delivered at < 37 weeks of gestation (42.7%, 54.2% vs. 91.4%, respectively, P < 0.05) and fetal survival rate (88.4%, 81.4% vs. 40.0%, respectively, P < 0.05). The history-indicated group and the ultrasound-indicated group were similar with regards to these outcomes. The independent risk factors affecting the clinical effects of cervical cerclage include age, body mass index (BMI), history of prior preterm birth and second-trimester loss, C-reactive protein (CRP) >5 mg/L and cervical dilation ≥3 cm (P < 0.05). Conclusion: Pregnancy outcomes were similar when compared between history-indicated and ultrasound-indicated cerclage. Serial cervical surveillance is beneficial for pregnant with a history of cervical insufficiency, and the placement of cervical cerclages in response to ultrasonographically detected shortening of the cervical length is a medically acceptable alternative to the use of history-indicated cerclage. Keywords: Cervical cerclage, History-indicated cerclage, Ultrasound-indicated cerclage, Physical examination-indicated cerclage, Surgical effect